Bobbin lace and upcycling: an innovation proposal (Revista de Ensino em Artes, Moda e Design, 2022)
Sustainability refers to the capacity of a process or system to sustain or conserve itself. In a world full of commodities and in an environment saturated with discards in limits no longer acceptable, the demand for sustainable scenarios requires changes in production and consumption patterns. In the Fashion area, sustainable development concerns a production model that reduces social and environmental impacts, avoiding the linear production format and seeking a circular alternative. Aligned with the precepts of sustainability and circular fashion, upcycling can be understood as an ecological alternative that gives new meaning and function to certain material that would be discarded. The purpose of this study is to present some key posts and relevant results of field research that sought to go through the path of bobbin lace in Florianopolis. In this sense, it is an applied research with the development of an innovation project, based on the Guideline for Project Development (GODP), in the projectual practice of Fashion Design that resulted in an adapted methodology of the project with a user-centered approach, in turn developed from the vocation and potential of local traditional crafts, the Bobbin Lace of Florianopolis, in the context of fashion and sustainability. From consultation with specific literature about the bobbin lace, the theoretical contributions about the Sustainability of projectual practice, combined with field research, the study demonstrates the breadth of Design activities and its potential as a strategic tool for sustainable development of the City of Florianopolis.
Keywords: bobbin lace; upcycling; innovation